Clarke, George (London, 2013)
2010 "Clarke, George", 2013, HistoryTalk George Clarke (1924-2015). George was born in 1924 in Deskford, North East Scotland. He worked as a forester and then served in the RAF during the war. Post-war he worked as a tram conductor and as a surveyor for the Ordnance Survey before, in 1949, changing jobs to work for the National Council of Labour Colleges, (NCLC), running evening classes, one-day and weekend schools throughout County Durham. He became the District Organiser for the NCLC in the North East of England and also, in 1954, was elected as a councillor for Gateshead Borough Council.